Calculated organ doses using Monte Carlo simulations in a reference male phantom undergoing HDR brachytherapy applied to localized prostate carcinoma. Issue 3 (27th February 2013) - Candela‐Juan, Cristian; Perez‐Calatayud, Jose; Ballester, Facundo; Rivard, Mark J.
Abstract : Purpose : : The aim of this study was to obtain equivalent doses in radiosensitive organs (aside from the bladder and rectum) when applying high‐dose‐rate (HDR) brachytherapy to a localized prostate carcinoma using 60 Co or 192 Ir sources. These data are compared with results in a water phantom and with expected values in an infinite water medium. A comparison with reported values from proton therapy and intensity‐modulated radiation therapy (IMRT) is also provided. Methods : : Monte Carlo simulations in Geant4 were performed using a voxelized phantom described in International Commission on Radiological Protection (ICRP) Publication 110, which reproduces masses and shapes from an adult reference man defined in ICRP Publication 89. Point sources of 60 Co or 192 Ir with photon energy spectra corresponding to those exiting their capsules were placed in the center of the prostate, and equivalent doses per clinical absorbed dose in this target organ were obtained in several radiosensitive organs. Values were corrected to account for clinical circumstances with the source located at various positions with differing dwell times throughout the prostate. This was repeated for a homogeneous water phantom. Results : : For the nearest organs considered (bladder, rectum, testes, small intestine, and colon), equivalent doses given by 60 Co source were smaller (8%–19%) than from 192 Ir. However, as the distance increases, the more penetrating gamma rays produced by 60 Co deliver higher organ equivalent doses. The overall result is that effective dose per clinical absorbed dose from a 60 Co source (11.1 mSv/Gy) is lower than from a 192 Ir source (13.2 mSv/Gy). On the other hand, equivalent doses were the same in the tissue and the homogeneous water phantom for those soft tissues closer to the prostate than about 30 cm. As the distance increased, the differences of photoelectric effect in water and soft tissue, and appearance of other materials such as air, bone, or lungs, produced variations between both phantoms which were at most 35% in the considered organ equivalent doses. Finally, effective doses per clinical absorbed dose from IMRT and proton therapy were comparable to those from both brachytherapy sources, with brachytherapy being advantageous over external beam radiation therapy for the furthest organs. Conclusions : : A database of organ equivalent doses when applying HDR brachytherapy to the prostate with either 60 Co or 192 Ir is provided. According to physical considerations, 192 Ir is dosimetrically advantageous over 60 Co sources at large distances, but not in the closest organs. Damage to distant healthy organs per clinical absorbed dose is lower with brachytherapy than with IMRT or protons, although the overall effective dose per Gy given to the prostate seems very similar. Given that there are several possible fractionation schemes, which result in different total amounts of therapeutic absorbed dose, advantage of a radiation treatment (according to equivalent dose to healthy organs) is treatment and facility dependent.